2000
DOI: 10.1002/1097-0193(200011)11:3<162::aid-hbm30>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Brain processing of visual sexual stimuli in human males

Abstract: Despite its critical sociobiological importance, the brain processing of visual sexual stimuli has not been characterized precisely in human beings. We used Positron Emission Tomography (PET) to investigate responses of regional cerebral blood flow (rCBF) in nine healthy males presented with visual sexual stimuli of graded intensity. Statistical Parametric Mapping was used to locate brain regions whose activation was associated with the presentation of the sexual stimuli and was correlated with markers of sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
396
1
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 473 publications
(449 citation statements)
references
References 60 publications
39
396
1
13
Order By: Relevance
“…For example, erotic stimuli elicit neuronal activities in brain areas commonly associated with the human reward system (e.g., Ishai, 2007;Karama et al, 2002;Mouras et al, 2003;Ponseti et al, 2006;Redouté et al, 2000;Safron et al, 2007;Stoléru et al, 1999). Visual stimuli of sexually attractive targets may also trigger schematic processes (e.g., evaluative, comparative, or associative processes, episodic memories, fantasizing).…”
Section: Stimulus-specific Processesmentioning
confidence: 99%
“…For example, erotic stimuli elicit neuronal activities in brain areas commonly associated with the human reward system (e.g., Ishai, 2007;Karama et al, 2002;Mouras et al, 2003;Ponseti et al, 2006;Redouté et al, 2000;Safron et al, 2007;Stoléru et al, 1999). Visual stimuli of sexually attractive targets may also trigger schematic processes (e.g., evaluative, comparative, or associative processes, episodic memories, fantasizing).…”
Section: Stimulus-specific Processesmentioning
confidence: 99%
“…However, a significant correlation ( Figure 5) was observed between total MGH-SFQ score and averaged parameter estimates obtained from the pMCC region (voxels significant in the omnibus F-test at po0.05 corrected). This region had been selected for further investigation based on previous literature showing correlations between brain activation in the MCC with behavioral measures of sexual functioning (Redoute et al, 2000;Moulier et al, 2006;Georgiadis et al, 2010). The more the brain activation decreased under paroxetine compared with placebo, the more overall ratings of sexual dysfunction (paroxetine minus placebo) increased (r ¼ 0.42; p ¼ 0.041).…”
Section: Neural Correlates Of Antidepressant-related Sexual Dysfunctimentioning
confidence: 99%
“…Activity of the pgACC has also been postulated to correlate with subjective sexual intensity and its hedonic value (Walter et al, 2008a) and was identified as a brain region specifically coding the interaction of sexual intensity and emotional value of a stimulus. In Redoute's model of sexual arousal, activation of rostral ACC, comprising subgenual and pregenual parts, has been ascribed to the autonomic component of sexual behavior mediating physiological readiness (Redoute et al, 2000). It is of note though that sgACC and pgACC have also been characterized as brain regions coding emotional contents in a wider context (Beckmann et al, 2009), of which autonomic reactions and self-referential processes may represent certain subsets.…”
Section: Blunted Anterior Cingulate Activation Under Paroxetinementioning
confidence: 99%
See 2 more Smart Citations